Severity and influencing factors of hyperprolactinemia in hospitalized schizophrenia patients: a cross-sectional study - Yang, Yan; Li, Li; Yang, Mi (Frontiers in Psychiatry, 2025)
ObjectiveTo investigate the severity and influencing factors of hyperprolactinemia (HPRL) in hospitalized schizophrenia patients.MethodsThis retrospective study enrolled schizophrenia inpatients from a tertiary psychiatric hospital (2022-2023) with monitored prolactin (PRL) levels. Participants were categorized into normal PRL, mild HPRL, moderate HPRL, and severe HPRL groups. Laboratory indices and medication information were collected, and an ordered logistic regression modeling was conducted to analyze the influence of HPRL severity.ResultsAmong 3,641 hospitalized schizophrenia patients, 2,519 (69.18%) underwent PRL monitoring during hospitalization. A total of 1,425 patients were included for HPRL severity analysis, with 903 (63.40%) exhibiting HPRL (mild: 52.05%, moderate: 30.01%, severe: 17.94%). The mean PRL level was 983.66 ± 1001.98 mIU/L, with severe HPRL reaching 3233.66 ± 1001.98 mIU/L. The ordered multivariate logistic regression model showed that HPRL severity was negatively correlated with aripiprazole use, male sex, fasting glucose, aspartate aminotransferase (AST), and follicle-stimulating hormone (FSH), but positively correlated with the use of sulpiride, paliperidone, amisulpride, risperidone, blonanserin, trihexyphenidyl, and anxiolytics.ConclusionHPRL is highly prevalent in schizophrenia patients, with distinct clinical profiles across severity levels. HPRL severity is associated with specific antipsychotics, anxiolytics, trihexyphenidyl, and metabolic indicators, underscoring the need for risk stratification and individualized management.